التحقيق في بعض المسائل الكلامية المنسوبة إلى المعتزلة - عزيز, حميد محمدأمين; علي, حكيم أبو بكر (Sulaimani Journal for Humanities, 2018)
This research is a study about an Islamic group in the name of Mu'tazila. This band appeared at the time of the succession of the Umayyads, and emerged on the Islamic scene strongly in the time of the Abbasids, and embraced by some caliphs as a doctrine for them. This doctrine is the first Islamice theology group to appear in Islam. The men of this doctrine tried to establish the intellectual bases in Islam, raised the mind and made it a prestigious place. . The researchers studied the origin of this doctrine, the history of their origin, and the reason for their designation as a Mu'tazila. And brought a number of opinions of scientists and researchers and orientalists in that, until they out to the result, namely: that this name was first launched on the group retired two rival groups of Muslims, the Sunnis and Khawarij, when someone makes a great sin , Khawarijs think that this person is an atheist,and Sunnis believe that this person is a punk, but the Mu'tazila stood in a middle position between them and said that he was in a position between the two houses, that is, the status of disbelief and faith. In this study, the researchers also explained the five origins of the doctrine of the Mu'tazilah, which are their principles, and the orbit of their doctrine. Then the researchers pointed on some positive and negative effects of this doctrine on Islamic thought and Muslims. In the second part of this research, the researchers selected a set of doctrinal questions attributed to this group in the books of articles and teams and books of the doctrines of other schools of thought, and investigated and examined them, by reference to the original sources of this doctrine. This study shows that there are doctrinal views attributed to the Mu'tazilat incorrectly, and that the imams of the Mu'tazilah have stated contrary to these beliefs and opinions, and have proven their righteousness. This study shows the reality of the percentage of these views of the Mu'tazili, and showed the fact of important doctrinal issues is taken for granted by many that the Mu'tazili believe. Then the researchers concluded their study with a conclusion in which the most important results reached by this study, The important point of these results is that the correct way to know the doctrines of any sect is only by reference to the books of the owners of this doctrine, not by reference to the books of their opponents and critics.